FEDERAL EXCISE TAX PROPOSAL FROM COALITION ON SMOKING OR HEALTH. (Tufts Archival Research Center, 2007)
Illegible/Difficult to Read; Memorandum from Samuel D. Chilcote Jr. to the executive board regarding a proposal by the Coalition on Smoking OR Health to increase the cigarette excise tax. Lists means of preventing passage of tax proposal through Congress.